The potential symbolism in James Joyce᾿s ”A Painful Case” (Philologia, 2021)
This paper analyses the significance of colours and certain places in James Joyce᾿s story ”A Painful Case”, and includes references to etymological roots. It also examines certain religious connotations and issues of sexuality and gender, the use of symbols and possible directions of interpreting the events and characters depicted.
Keywords: symbolism; colours; dark; black; sexuality; religion; paralysis